Let Me Write - Murray, W.; Illustrated by Aitchison, M. (London Ladybird)
Uses some of the most frequently met words in the English language as a starting point for learning to read successfully and confidently. This book encourages writing skills and introduces 36 new words such as 'rabbit', 'flowers' and 'train'.
Include Color Illustrations